Barriers to Pediatric Disaster Triage: A Qualitative Investigation. (3rd April 2015) - Koziel, Jeannette R.; Meckler, Garth; Brown, Linda; Acker, David; Torino, Michael; Walsh, Barbara; Cicero, Mark X.
Abstract: Background. In disasters, paramedics often triage victims, including children. Little is known about obstacles paramedics face when performing pediatric disaster triage.Objective. To determine obstacles to pediatric disaster triage performance for paramedics enrolled in a simulation-based disaster curriculum.Design. We conducted a qualitative evaluation of paramedics' self-reported obstacles to pediatric disaster triage performance. The paramedics were enrolled in a pediatric disaster triage curriculum at one of three study sites. An individually administered, semi-structured debriefing was created iteratively, and used after a 10-victim, multiple-family house fire simulation. The debriefings were audio-recorded, and transcribed. Two investigators independently analyzed the transcripts. Using grounded theory strategy, the data were analyzed via 1) immersion and coding of data, 2) clustering of codes to generate themes, and 3) theme-based generation of hypotheses. While analyzing the data, we employed peer debriefing to determine emerging codes, groups, and thematic saturation. Systematically applied data trustworthiness strategies included triangulation and member checking.Results. A total of 34 participants were debriefed, with prehospital care experience ranging from 1 to 25 years of experience. We identified several barriers to pediatric disaster triage: 1) lack of familiarity with children and their physiology, 2) challenges with triaging children with special health-care needs, 3) emotional reactions to triage situations, including a mother holding an injured/dead child, and 4) training limitations, including poor simulation fidelity.Conclusion. Paramedics report particular difficulty triaging multiple child disaster victims due to emotional obstacles, unfamiliarity with pediatric physiology, and struggles with triage rationale and efficiency.